The use of acoustic Doppler sensors to improve flow measurements during drought conditions in Spain - Cook, M. J., author; Tarafa, Neus, author; Bueno, Felix, author; Alonso-Martirena, Andrés, author; Villegas, Juan José, author; U.S. Committee on Irrigation and Drainage, publisher (Colorado State University. Libraries, 2010)
In recent years, the northeast region of the Iberian Peninsula has experienced extreme drought, thus creating a need for water managers to have a better understanding of the available water resources. In the spring of 2007, the Agencia Catalana de l'Aigua (ACA) contracted Qualitas Instruments, SA to install five pulsed acoustic Doppler profilers at key sites near Girona, Spain with the goal of obtaining more accurate open channel flow measurements. In the past, these sites used water level as a surrogate to measure flow, however due to site conditions, rating curves at the site did not provide sufficient flow accuracy. In the scenarios presented in this paper, backwater effects from irrigation gates and water control structures in streams had an influence on flow monitoring at the sites. Rating curves typically break down in these situations because each water level does not have a unique associated flow value; that is to say for a given water level, there may be multiple flow values. Doppler sensors measure water depth and a velocity profile. Water depth data is used to determine flow area, which is multiplied by the average velocity that is measured by the Doppler sensor ultimately providing increased resolution and accuracy on flow measurements. Preliminary data indicate that for two sites (Canal Vinyals and Sentmenat), the rating curve method overestimated low flows conditions by an average of 68%, while the rating curve method at Resclosa Canet underestimated flows by 25%. Another irrigation canal, Canal Marge Esquerra, the Doppler sensor and Rating Curve provided similar data. Additionally, a stream monitoring site that applied a rating curve measured well during base flow, but was found to underestimate high flow conditions by approximately 31% when compared to the acoustic Doppler instrument, therefore additional investigations are needed for the site.
USCID water management conference
Acoustic Doppler sensors
Presented at Upgrading technology and infrastructure in a finance-challenged economy: a USCID water management conference held on March 23-26, 2010 in Sacramento, California.